Trust and trustworthy computing : 8th International Conference, TRUST 2015, Heraklion, Greece, August 24-26, 2015, Proceedings /: 8th International Conference, TRUST 2015, Heraklion, Greece, August 24-26, 2015, Proceedings. (2015) - Unknown
No abstract available